Growth performance of yearling F1 progeny of different crossbred beef cattle - Mostari, MP; Khan, MYA; Roy, BK; Hossain, SMJ; Huque, KS (Bangladesh Journal of Animal Science, 2017)
Bangladesh has a great demand of beef but it has been facing demand and supply mismatches due to insufficient production and supply of beef, low carcass yield of native cattle and recent no-cattle export policy of a long bordered neighboring country. Thus, the present work was undertaken with an objective to develop market beef cattle of average >150 Kg carcass weight by 24 months with an average FCR of <6.50 under on farm feeding and management condition. Aiming at developing breeding bulls the native dams of BCB-1 (BLRI Cattle Breed 1) were inseminated with the imported frozen semen of Brahman, Simmental, Charolais and Limousin. The crossbred progeny of different assorted F1 genotypes were being selected and their production and breeding performance were evaluated and compared with BCB-1. All pregnant (> 6 months of gestation period) cows were in pre-natal care, and all calves were raised in a single plane of nutrition and management. All crossbred progeny performed better than BCB-1 in terms of live weights and average daily gains. Among the crossbreds, Charolais×BCB-1 had the highest (p<0.001) birth weight (27.5±1.52 kg) followed by Brahman×BCB-1 (24.1±1.23), Simmental×BCB-1 (21.9±1.78), Limousin×BCB-1 (19.8±1.39) and BCB-1×BCB-1 (18.4±1.09), and the genotypes differences were highly significant (p<0.001). In average growth curve, Simmental cross grew faster followed by Charolais, Limousin, Brahman crosses and purebred BCB-1. The genotype×environment interaction was only observed in birth weight. Purebred BCB-1 had the lowest daily DM intake and showed the lowest FCR in all ages compare to other crosses. Calf scour and alopecia occurred in all genotypes. In this breeding program, calf mortality was found as 5.26%. Simmental×BCB-1 is performing as the best among the five genotypes in terms of growth up to 12 month of age. Bang. J. Anim. Sci. 2017. 46 (2): 82-87